Identification of microRNA Transcriptome Involved in Bovine Intramuscular Fat Deposition - Duckett, Susan K.; Greene, Maslyn A. (Frontiers in Veterinary Science, 2022)
Background: Intramuscular fat deposition in beef is a major determinant of carcass quality and value in the US. The objective of this study was to examine changes in microRNA (miRNA) transcriptome that are involved with intramuscular fat deposition with time-on-concentrates (TOC). Yearling steers were individually fed a high concentrate diet and changes in intramuscular fat deposition were monitored by real-time ultrasound at 28 to 33 d intervals. Longissimus muscle biopsies collected on d 0, 92 and 124 TOC to examine changes in miRNA transcriptome that are involved in intramuscular fat deposition. Results: Steer body weight increased (P < 0.0001) at each weigh day during TOC. Fat thickness increased (P < 0.005) from d 28 to 124. Ribeye area was larger (P < 0.001) on d 124 than d 61, which was larger than d 0 and 28. Ultrasound intramuscular fat content was greater (P < 0.001) on d 92 and 124 compared to d 0, 28 or 61. Sequencing of the muscle biopsy samples identified one miRNA, bta-miR-122, that was up-regulated (P < 0.005) at d 92 and 124 compared to d 0. At d 92 TOC, mRNA expression levels of fatty acid binding protein 4 (FABP4) and elongase 6 (ELOVL6) were up-regulated (P < 0.01) compared to d 0; whereas at d 124, lipogenic genes involved in de novo fatty acid synthesis, fatty acid transport, elongation and desaturation were highly up-regulated compared to d0. Conclusions: We identified bta-miR-122 as a key miRNA involved in intramuscular fat deposition with increasing TOC. Increased intramuscular fat content, as measured by real-time ultrasound, combined with differential gene expression suggests that preadipocyte differentiation may be stimulated first, which is followed by a global up-regulation of lipogenic genes involved in de novo fatty acid synthesis that provide fatty acids for subsequent hypertrophy.